Effects of Lighting Programmes on Growth and Laying Performance of the Native Chicken - Ratana Chotesangasa; Pinate Santipong (Agriculture and Natural Resources, 1994)
An experiment was conducted to determine the effect of three lighting programmes on growth, laying performance, mortality rate and egg component in the native chicken. The three lighting programmes were : (a) the natural photoperiod during both growing and laying periods (group 12L,12L) the natural photoperiod during growing period and the photoperiod of 15 hours/day during laying period (group 12L,15L), and (c) the photoperiod of 8 hours/day during growing period and 15 hours/day during laying period (group 8L,15L). Average body weight gains, feed conversion ratios and prelaying mortality rates during growing period of three groups were not different (P>0.05). Of the 8L,15L group, 12L,15L group and 12L,12L group, ages at the onset of lay were 165.8, 171.8, and 188.8 days (P<0.05); body weights at the onset of lay were 1.5, 1.6, and 1.8 kilograms (P<0.05); and their first egg weights were 31.4, 34.7, and 35.7 grams (P<0.05), respectively. Percentages of hen-day egg production measured at 2-week intervals of the 8L,15L hen were higher (P<0.05) or tended to be higher than those of the other 2 groups. In term of cumulative egg production, the 8L,15L hen peoduced 70.7 eggs/hen/28 weeks which was higher than (P<0.05) 50.6 and 45.0 eggs/hen/28 weeks of the 12L,15L and 12L,12L hens, respectively. In general, the three different lighting programmes had no ong-term effect on feed conversion ratio in the native hen though different values (P<0.05) were sometimes observed in the early laying period. Laying mortality rate of the 8L,15L group was 40.9% which was higher than (P<0.05) 26.2% and 23.9% of the 12L,15L and 12L,12L groups, respectively. Average egg weights presented at 2-week intervals of the 8L,15L hen were lower or tended to be lower than those of the 12L,15L and 12L,12L hens almost throughout the laying period. The higher yolk percentage and lower albumen + shell percentage of the 8L,15L native hen were suggested to be the consequence of its imbalanced-increased function of the albumen + shell secreting oviduct to the yolk-ovulation ovary.